The Maritime Strategy of Queen Kalinyamat in Shaping the Demak-Jepara Sultanate, 1549–1579 - Imas Emalia; Didik Pradjoko (JURNAL JAWI, 2025)
This study examines the maritime power exercised by the local rulers of Jepara between 1549 and 1579, who continued the legacy of the Demak Sultanate. Employing historical methods from a maritime perspective and drawing upon Alfred T. Mahan’s theory of sea power, this research explores how maritime strategy shaped the political and economic strength of Jepara. Although the Demak Sultanate formally ended with the death of Sultan Trenggana in the 16th century, Retna Kencana continued its legacy and later became known as Queen Kalinyamat. She became the first Muslim queen (sulṭānah) in Java. She developed a strategic approach to governance that utilized the sea as both a political and economic defense. The sea was viewed as a strategic arena for consolidating power and establishing economic relations with kingdoms beyond Java, such as Malacca, Aceh, and the Moluccas. Kalinyamat made the ports of Gresik and Jepara the maritime axis of Java, serving as gateways for trade between the eastern and western regions of the island. Through her political and economic policies, she launched major naval expeditions to Malacca and the Moluccas, aimed at defending maritime territories and curbing Portuguese economic activities along Java’s northern coast. These strategies are believed to have weakened Portuguese influence in the archipelago. Historical records portray Jepara as a center of maritime glory and Kalinyamat as a courageous Javanese ruler, celebrated even by the Portuguese, who referred to her as “de Kranige Dame” (the Courageous Lady).‎